THE PROBLEM OF SPURIOUS DRUGS IN PAKISTAN: NEED OF GOVERNMENT INTERVENTION AND PROTECTION OF CONSUMER RIGHTS - Ms. Rooshaney Salim, Dr. Fiaz Hussain (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Consumer laws are comparatively weak in developing nations including Pakistan. This not only affects the economy but, in some case, causes severe health hazards. Spurious drugs is a phenomena prevailing in the whole world but the worst case scenarios are found in developing nation like Pakistan.It is reported that 6-10% of cross border trade in medicines in developing countries comprises of counterfeit medicines. It is alleged that Pakistani market has almost 50 % spurious drugs. Thesespurious drugs are fake medicines which are made to imitate the genuine. This is not only a crime against economy but also against public health. With this background, this study aims to gauge the level of awareness among different segments of society, to find out the contributing factors to this problem and possible remedies to counter the problem. Primary data was collected using structured questionnaires from the consumers, healthcare professionals, retailers and wholesalers. Purpose sampling technique was used to collect data from 200 respondents. The statistical results show that the most contributing factors are no law enforcement and weak legislation while the most effectiveremedies to solve the problem of growth of spurious drugs are severe and enhanced punishment for the culprits and enforcement of laws, as well as random inspections at drugs outlets.